HUBUNGAN TINGKAT PENGETAHUAN TENTANG INTENSIVE CARE UNIT (ICU) DENGAN KECEMASAN PADA KELUARGA YANG DIRAWAT DI RUANG ICU RSUD Dr. HARJONO S PONOROGO - Khrisna Indah Mardiasih; Oktaffrastya Widhamurti Septafani (LPPM STIKes SATRIA BHAKTI NGANJUK, 2026)
Patients treated in the ICU are in critical condition. Thiscondition causes families to experience a variety of feelings and emotionalreactions, resulting in anxiety. Incorrect or inadequate knowledge about ICU careprocedures can increase family anxiety. This study aims to determine therelationship between knowledge levels about the Intensive Care Unit (ICU) andanxiety in families treated in the ICU at Dr. Harjono S Ponorogo RegionalHospital